(untitled) (Eurasian Journal of Philology Science and Education, 2018)
This article examines a new facet of the works of K. Nurmakhanov. The author analyzes his activity with young writers, as they, in his opinion, are «reserve of Kazakh literature». The critic took care of continuous replenishment in the literature of new talented creative forces. Carefully directing the activities of a talented writer, he remembered about the vulnerability of the author, about the defenselessness under adverse circumstances as well as reckless, unfair words. The author also notes that K. Nurmakhanov underlined the important role of literary publishing houses that should help literary youth differentiate requirements for both a novice author and a writer of the older generation.